خوارزمية كمومية لحل مشاكل البحث في فضاءات البحث غير البنيوية - البستاني, حسن; غانم, يانا (Latakia University Journal -Engineering Sciences Series, 2019)
Grover algorithm is a quantum algorithm for solving search problems in unstructured databases which means that finding that one of the elements in the search space isn’t a solution can’t help us to avoid looking at other elements,this case is the most difficult, as to find the owner of a given telephone number in a phonebook arranged by names whereas the easiest case is to search in a structured search space,such as to search for a phone number for a given person in a phonebook arranged by names. This paper discusses the formation of this algorithm- which provides a polynominal (quadratic) acceleration compared to classical search algorithm- using quantum gates and its implementation in a 16-elements search space to search for different numbers and values of solutions. إنّ خوارزمية كروفر هي خوارزمية كمومية لحل مسائل البحث في فضاءات البحث غير البنيوية, ويقصد بفضاء البحث الذي ليس له بنية أنّ اكتشاف أنّ أحد الاحتمالات الواردة في فضاء البحث لا يمثل حلاً لا يمكننا من تجنب البحث في احتمالات أخرى(أي لا يمكن توجيه البحث لاحتمالات معينة بهدف تسريعه), وهذه الحالة هي الأصعب كمحاولة البحث عن اسم صاحب رقم هاتفي معطى في دليل هاتفي مرتّب بالأسماء, أما الحالة الأسهل فهي البحث في فضاء بحث ذي بنية, مثل البحث عن رقم هاتف لشخص معطى اسمه في دليل هاتفي مرتّب بالأسماء. تناقش ورقة البحث تشكيل هذه الخوارزمية - التي تؤمن تسريعاً تربيعياً بالمقارنة مع خوارزميات البحث التقليدية- باستخدام البوابات الكمومية وتنفيذها في فضاء بحث من 16 عنصر للبحث عن أعداد وقيم مختلفة من الحلول.